How do people already out of employment fare when the state pension age rises? - Jonathan Cribb; Anna Henry; Heidi Karjalainen (Institute for Fiscal Studies (IFS), 2025)
The state pension age (SPA) for women rose from 60 to 66 between 2010 and 2020 (and for men from 65 to 66 between 2018 and 2020). Further increases to the SPA (for both men and women) are legislated starting from next year, such that it reaches 67 in early 2028. Understanding the effects of previous increases in the SPA is crucial for informing policymakers of the potential effects of future increases. This report focuses in particular on a group disproportionately affected by SPA increases: those who are already not in paid work prior to the SPA rise occurring.
Keywords: 330; Employment and income; Savings; pensions and wealth; Ageing; Pensioner benefits; Public finance; Retirement; State pensions; Gender